ANALISIS PENATALAKSANAAN GIZI BALITA STUNTING PADA MASA PANDEMI COVID-19 DENGAN METODE ANALYTIC HIERARCHY PROCESS(AHP) DI PUSKESMAS MUARA BASUNG - Sumengen, Sumengen; Melati, Rima; Hartono, Budi; Mahyuddin, Meriwati; Yunita, Jasrida (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
ABSTRACT Nutritional status in children under five is very important, if malnutrition occurs and if not treated immediately it will reduce the quality of human resources resulting in physical disorders, impaired intelligence and productivity. The COVID-19 pandemic increases the risk of an increase in the prevalence of stunting. The purpose of this study was to analyze the nutritional management of stunting toddlers during the COVID-19 pandemic using the Analytic Hierarchy Process (AHP) method at the X Health centre, Bengkalis Regency based on input, process and output components. Method: This study used a qualitative approach using the analytic hierarchy process method. Data collection methods were carried out by in-depth interviews and observations to 15 informants, consisting of the administrative head of the Health Centre, nutrition officers, MCH coordinator midwife, village midwife, posyandu cadres and mothers of stunting toddlers. Result: showed that at the input stage, health workers such as TPG and village midwives had met the competency requirements, there were no special appointments for stunting cadres and specific technical guidelines for stunting management, as well as the lack of infrastructure for monitoring growth and development in Posyandu. Implemented properly include antenatal care, supplementary feeding, vitamin A administration, the coverage of which is still low is exclusive breastfeeding and visits to Posyandu. In the output element, the prevalence of stunting at the X Health Center in 2020 reached 15.02%Keyword : AHP, Management of stunting, Covid 19